EFEKTIVITAS UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERKAWINAN TERHADAP PROSES DISPENSASI PERKAWINAN ANAK DIBAWAH UMUR DI DESA SIDETAPA (STUDI KASUS PENGADILAN NEGERI SINGARAJA) - Ni Desak Kadek Arianti; I Nengah Suastika; Komang Febrinayanti Dantes (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aims to examine and find out about the legal consequences of marriage dispensation in Sidetapa Village and to review and find out the effectiveness of Law Number 16 of 2019 concerning Marriage related to the existence of a dispensation for marriage of minors in Sidetapa Village, Banjar District, Buleleng Regency. The type of research used is empirical juridical. This research is descriptive. The location of this study is Sidetapa Village and Singaraja District Court. The informants of this study were to the Head of Sidetapa Village, the Sidetapa Village Community, and the Chairman of the Singaraja District Court. Data collection techniques are carried out by observation techniques, interviews and document studies, which later the data obtained will be analyzed descriptively. The results show that the legal consequences of the marriage dispensation in Sidetapa Village, people who carry out underage marriages and parents do not apply for dispensation, the child born by their mother will not be able to have complete papers, besides that it will be difficult to make administration such as Marriage Certificates, Identity Cards, Family Cards. And the application of the marriage dispensation rules for underage marriages contained in Article 7 of Law Number 16 of 2019 concerning Marriage has not been effectively applied in Sidetapa Village, the ineffectiveness of the rule can be reviewed from two things, namely in terms of community understanding of the rules of marriage dispensation, and there is no socialization from the apparatus that applies the dispensation rules to Sidetapa Village.